Protein arginine methyltransferase 6 mediates cardiac hypertrophy by differential regulation of histone H3 arginine methylation - Vineesh Vimala Raveendran; Kamar Al-Haffar; Muhammed Kunhi; Karim Belhaj; Walid Al-Habeeb; Jehad Al-Buraiki; Atli Eyjolsson; Coralie Poizat (Heliyon, 2020)
Heart failure remains a major cause of hospitalization and death worldwide. Heart failure can be caused by abnormalities in the epigenome resulting from dysregulation of histone-modifying enzymes. While chromatin enzymes catalyzing lysine acetylation and methylation of histones have been the topic of many investigations, the role of arginine methyltransferases has been overlooked. In an effort to understand regulatory mechanisms implicated in cardiac hypertrophy and heart failure, we assessed the expression of protein arginine methyltransferases (PRMTs) in the left ventricle of failing human hearts and control hearts. Our results show a significant up-regulation of protein arginine methyltransferase 6 (PRMT6) in failing human hearts compared to control hearts, which also occurs in the early phase of cardiac hypertrophy in mouse hearts subjected to pressure overload hypertrophy induced by trans-aortic constriction (TAC), and in neonatal rat ventricular myocytes (NRVM) stimulated with the hypertrophic agonist phenylephrine (PE). These changes are associated with a significant increase in arginine 2 asymmetric methylation of histone H3 (H3R2Me2a) and reduced lysine 4 tri-methylation of H3 (H3K4Me3) observed both in NRVM and in vivo. Importantly, forced expression of PRMT6 in NRVM enhances the expression of the hypertrophic marker, atrial natriuretic peptide (ANP). Conversely, specific silencing of PRMT6 reduces ANP protein expression and cell size, indicating that PRMT6 is critical for the PE-mediated hypertrophic response. Silencing of PRMT6 reduces H3R2Me2a, a mark normally associated with transcriptional repression. Furthermore, evaluation of cardiac contractility and global ion channel activity in live NRVM shows a striking reduction of spontaneous beating rates and prolongation of extra-cellular field potentials in cells expressing low-level PRMT6. Altogether, our results indicate that PRMT6 is a critical regulator of cardiac hypertrophy, implicating H3R2Me2a as an important histone modification. This study identifies PRMT6 as a new epigenetic regulator and suggests a new point of control in chromatin to inhibit pathological cardiac remodeling.